Optimizing Supply Chain Management for Processed Shallot Products: Case Study at PT. Innovative Brebes Synergy - Halisa, Sindy Amany Nur; Adita, M. Dini (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Supply Chain Management or supply chain management is a collection of activities in the form of units/facilities involved in the production and distribution process of goods from raw materials to finished products to end users. PT. Brebes Innovative Synergy is a company operating in the agricultural sector, a company owned and managed by a farmer group, namely the Sidomakmur Farmer Group, which produces processed shallots. This observation aims to determine the optimization of the Supply Chain Management (SCM) system for processed shallot products at PT. Innovative Brebes Synergy. This observation uses data collection methods which include observation, interviews and literature study. Results of observations on Field Work Practice activities at PT. Innovative Brebes Synergy in the first hypothesis shows that Supply Chain Management (SCM) of processed shallot products through products, prices, distribution, promotions, processes, human resources and infrastructure of PT. This Innovative Brebes Synergy focuses on implementing sustainability principles, committed to providing quality and satisfaction to consumers in the form of shallot products that are the best, hygienic and safe for consumption. Apart from that, this processed shallot product has been integrated with various e-commerce and the central government. thus producing quality and functional products. Meanwhile, the results of the observation of the second are that the optimization of supply chain management carried out by the company in terms of raw materials has not yet reached optimal with an MVPXi / PXi ratio value of 1.00107, but in terms of product marketing it has reached optimal marketing with an MVPXi / PXi ratio value of 1.